Fairy tales transformed? : twenty-first-century adaptations and the politics of wonder - Bacchilega, Cristina, 1955- (Wayne State University Press Detroit, 2013)
"Fairy-tale adaptations are ubiquitous in modern popular culture, but readers and scholars alike may take for granted the many voices and traditions folded into today's tales. In Fairy Tales Transformed?: Twenty-First-Century Adaptations and the Politics of Wonder, accomplished fairy-tale scholar Cristina Bacchilega traces what she terms a "fairy-tale web" of multivocal influences in modern adaptations, asking how tales have been changed by and for the early twenty-first century. Dealing mainly with literary and cinematic adaptations for adults and young adults, Bacchilega investigates the linked and yet divergent social projects these fairy tales imagine, their participation and competition in multiple genre and media systems, and their relation to a politics of wonder that contests a naturalized hierarchy of Euro-American literary fairy tale over folktale and other wonder genres."-- Resumé vydavatele
Keywords: 21. století; pohádky; pohádky -- dějiny; filmové adaptace -- 21. století; filmové pohádky -- 21. století; fairy tales; fairy tales -- history; film adaptations -- 21st century; fairy tales (film adaptations) -- 21st century; monografie; elektronické knihy; monographs; electronic books